The nutritional benefits of cash transfers in humanitarian crises: Evidence from Yemen - Kurdi, Sikandra (Elsevier, 2021)
At the World Humanitarian Summit in 2016 the long-standing divide between humanitarian and development approaches was challenged with a call for responses that both meet immediate needs and protect human capital for eventual recovery. In this regard, the use of cash transfers in humanitarian settings is an emerging trend; however, it has been limited by a lack of evidence on how well cash transfers improve nutritional outcomes given the challenges of conducting rigorous evaluations in a crisis context. This study makes use of a cluster randomized control trial that was left in place when a pilot cash-plus intervention evolved during the civil conflict into a major program within the Yemen Emergency Crisis Response program. The results provide uniquely rigorous evidence of the potential for long-run nutritional benefits of cash transfers in humanitarian crisis settings. The “Cash for Nutrition” intervention provides cash transfers as well as nutritional training to targeted households with young children in Yemen in the context of what is considered the world’s worst humanitarian crisis. Differences-in-differences estimates indicate that the intervention significantly increased purchases of non-staple foods which translated into large positive impacts on child dietary diversity scores. Impacts on consumption patterns and dietary diversity are significant for the full sample and strongest among the poorest tercile of households where the transfers are largest relative to baseline household food budgets. In this poorest sub-group we also find large and statistically significant program impacts on height-for-age z-scores of 0.3. These results support the increased use of cash transfers and provide a benchmark for comparison with more traditional food distribution and supplementation strategies for supporting child nutrition in protracted crisis contexts.